Pengembangan Lembar Kerja Peserta Didik (LKPD) Interaktif Berbasis Komputer untuk Pembelajaran Sistem Periodik Unsur Kelas X SMA - Lailatur Rokhmah; Fakhili Gulӧ; Rodi Edi (Seminar Nasional Pendidikan IPA Tahun 2021, 2021)
Development of interactive student worksheet has been conducted and applied to learning the periodic system of elements in class X IPA SMA IslamAz-Zahrah Palembang. Development was done by using a modified ADDIE model with formative evaluation of Tessmer with stages of analysis, design, development, self evaluation, one to one, small group and field test. Data were collected throgh interviews, expert review, questionnaires and tests. The validity of interactive student worksheet scored by two expert of material, expert of media and expert of pedagogic. Value of material validity of 0.78 with high validity category, value of media validity of 0.73 with high validity category and value of pedagogic validity of 0.88 with high validity category. Average validity score of 0.80 with high validity category. Practicality of interactive student worksheet seen from questionnaire at one to one and small group. Obtained the average practice questionnaire score of 0,83 with high practicality category. The effectiveness of interactif student worksheet measured from student learning outcomes at field test stage, obtained N-gain of 0.76 with high effectiveness categories. The Result of research produce an interactive student worksheet that meets the very valid, very practical and very effective criteria for the learning of the periodic elements system